Harvesting hope : the story of Cesar Chavez - Krull, Kathleen; Morales, Yuyi (San Diego : Harcourt, inc., 2003)
A biography of Cesar Chavez, from age ten when he and his family lived happily on their Arizona ranch, to age thirty -eight when he led a peaceful protest against California migrant workers' miserable working conditions
Keywords: Chavez, Cesar, -- 1927- -- Juvenile literature; Chavez, Cesar, -- 1927-; United Farm Workers -- History -- Juvenile literature; United Farm Workers; Mexican Americans -- Biography -- Juvenile literature; Labor leaders -- United States -- Biography -- Juvenile literature; Labor leaders; Mexican Americans -- Biography; Migrant labor